A comparative analysis of dietary intakes during pregnancy in Europe: a planned pooled analysis of birth cohort studies(1)(2)(3)(4) - Mendez, Michelle A (American Society for Nutrition, 2011)
Background: There is growing evidence that despite the absence of marked deficiencies, diet during pregnancy has important implications for maternal and child health in industrialized countries. At present, relatively little is known about prevailing patterns of intake across groups with diverse sociodemographic and lifestyle patterns in these settings. Objectives: The aims of this study were to develop methods for the standardization of food group intake data and to describe the process of applying these methods to existing pregnancy cohort studies, which included >200,000 women across Europe. Design: The study developed a detailed standardization protocol to harmonize intakes of selected food groups, which included fruit, vegetables, meats, seafood, and dairy products. Standardization is necessary to facilitate valid comparisons of intake patterns and disparities across countries and will lead to the development of harmonized databases for possible future pooled analyses. Results: On the basis of comparisons with previously coordinated multicountry studies, preliminary data suggest that the standardization process yielded sufficiently comparable intake data, which indicate differences in food cultures across the countries that participated. Conclusions: This project provides lessons on the feasibility of harmonizing dietary intake data from existing studies, which can be applied in future post hoc standardization efforts. The data yielded in this analysis will also provide useful information for the development of food and nutrition policies for pregnant women in Europe, including the identification of population subgroups in which dietary inadequacies during pregnancy may be widespread.